Westward Acceleration of Tropical Stratopause Zonal Winds During Major Sudden Stratospheric Warming Events - N. Koushik; Karanam Kishore Kumar; Tarique A. Siddiqui (Geophysical Research Letters)
Abstract The tropical Mesosphere‐Lower Thermosphere‐Ionosphere system is found to show significant variabilities during Sudden Stratospheric Warming (SSW) events. Recent studies have highlighted the possible role played by modified background wind conditions in communicating the SSW‐induced stratospheric perturbations to the Mesosphere‐Lower Thermosphere‐Ionosphere region. In the present study, changes in the background zonal winds at the tropical stratopause during major SSW events inferred from MERRA‐2 reanalysis data sets, rocket observations, and model simulations are reported for the first time. The tropical stratopause shows enhanced westward winds during the course of major SSW events. Rocketsonde observations from a low latitude station Thumba (8.5 ° N,76.9 ° E) also showed significant westward acceleration during three major SSW events. Further, Specified Dynamics version of the Whole Atmosphere Community Climate Model simulations for the 2008–2009 SSW replicate the observed features.